Associations of adverse childhood experiences with stress physiology and insulin resistance in adolescents at risk for adult obesity. Issue 6 (15th May 2021) - Jimenez, Virginia; Sanchez, Natalia; Clark, Emma L. M.; Miller, Reagan L.; Casamassima, Milena; Verros, Megan; Conte, Isabella; Ruiz‐Jaquez, Metztli; Gulley, Lauren D.; Johnson, Sarah A.; Melby, Christopher; Lucas‐Thompson, Rachel G.; et al.
Abstract: Adverse childhood experiences (ACEs) heighten the risk for adult obesity and cardiometabolic disease, but physiological factors underlying this connection are not well understood. We determined if ACEs were associated with physiological stress response and insulin resistance in adolescents at risk for adult obesity. Participants were 90 adolescents 12.0–17.5 years (50% female, 30% Hispanic/Latinx), at risk for adult obesity by virtue of above‐average body mass index (BMI; kg/m 2 ≥ 70th percentile) or parental obesity (BMI ≥ 30 kg/m 2 ). ACEs were determined as presence (vs. absence) based upon the Schedule for Affective Disorders and Schizophrenia for School‐Aged Children. Physiological stress response was measured as heart rate/blood pressure response to the Trier Social Stress Test. Homeostatic model assessment of insulin resistance was determined from fasting glucose/insulin. Sixty‐one percent of adolescents reported positive ACE history. The presence of ACEs predicted greater heart rate ( p < .001) and diastolic blood pressure ( p = .02) response to stress, controlling for age, sex, race/ethnicity, puberty, and BMI standard score. Systolic blood pressure and insulin resistance did not differ by ACE history ( p ‐values > .08). Findings suggest heightened sympathetic stress response in adolescence could be explanatory in how ACEs increase the risk for later cardiometabolic disease. Future studies should characterize ACEs in relationship to day‐to‐day variations in adolescents' stress physiology and glucose homeostasis.